Aulas de Campo em Ecossistemas Naturais da restinga de Ilha Comprida/SP e o Ensino e Aprendizagem de Biologia / Pratice lessons in Natural Ecosystems of sand-banks in Ilha Comprida/SP and Biology Learning and Teaching - Fonseca, Gustavo; de Andrade Caldeira, Ana Maria (Revista Internacional de Aprendizaje en Ciencia, Matemáticas y Tecnología, 2015)
ABSTRACT This study aims to investigate how lessons Field Practices in Terrestrial Ecosystems can contribute to the process of education and high school students of Ecology of Learning. We will seek to highlight how these activities can contribute to the construction of problematizations and Learning generating questions. For this we follow the process of signification ecological concepts developed in Campo classes in Natural Ecosystems. The research activities were held with high school students in the discipline of biology in a state school in the city of Ilha Comprida / SP. In this research work with ecological concepts planned for the high school. The didactic sequence presented involved the presentation of natural phenomena. The project generator theme were the Terrestrial Ecosystem Ilha Comprida. Because it is an island sandbank presents many coastal ecosystems of the Atlantic Forest with unique characteristics. Close spatially and physically limited on the northwestern coast by the Small Sea (estuary) and the southeast coast of the Atlantic Ocean. The city has well preserved vegetation. This makes Long Island a great "lab" didactic for teaching ecology of learning. RESUMO Este trabalho tem como objetivo investigar como as Aulas Práticas de Campo em Ecossistemas Terrestres podem contribuir para o processo de Ensino e Aprendizagem de Ecologia de estudantes do ensino médio. Buscaremos evidenciar como essas atividades podem contribuir para a construção de problematizações e perguntas geradoras de Aprendizagem. Para isso acompanhamos o processo de significação de conceitos ecológicos desenvolvidos em Aulas de Campo em Ecossistemas Natu-rais. As atividades de pesquisa foram realizadas com os alunos de ensino médio na disciplina de Biologia numa Escola Estadual no município de Ilha Comprida/SP. Nesta pesquisa trabalhamos com os conceitos de ecologia previstos para o ensino médio. A sequência didática apresentada envolveu a apresentação de fenômenos naturais. O tema gerador do projeto foram os Ecossis-temas Terrestres de Ilha Comprida. Por se tratar de uma ilha de restinga, apresenta diversos ecossistemas costeiros de Mata Atlântica com características singulares. Próximos espacialmente, e limitados fisicamente na costa noroeste pelo Mar Pequeno (estuário) e na costa sudeste pelo Oceano Atlântico. O município apresenta cobertura vegetal bem conservada. Tudo isto torna Ilha Comprida um ótimo “laboratório” didático para o ensino aprendizagem de ecologia. Contato principal: fonseca.guh@gmail.com